Prevalence of Frozen Shoulder among Patients Undergoing Cardiothoracic Surgery (Ibrahim Cardiac Medical Journal, 2011)
Keywords: Frozen shoulder; cardiothoracic surgery; physiotherapy; treatment complianceIbrahim Card Med J 2011; 1(1):14-16